Descriptive review curriculum study of vocational education in electrical engineering - Frismelly, Arinda; Sari, Fenti Amelia (Universitas Negeri Padang, 2025)
Educational institutions aim to produce the best professional graduates in their fields. Educational institutions cannot achieve these goals by themselves, they need the participation of the community. This situation forces education to continue to be sensitive to the needs of society, the demands of the times and government policies and to anticipate them by continuing to improve various related components in it. One of the components involved in the framework of the education system is the curriculum. This research is descriptive qualitative which aims to find out the picture, situation, a thing by describing it in as much detail as possible according to the existing facts of the Electrical Engineering Vocational Education curriculum. The results of this study indicated that the curriculum structure of the electrical engineering vocational education study program has characteristics based on the composition of the course consisting of general courses, engineering courses, and professional expertise courses. Based on the study material, engineering courses can be grouped into mandatory engineering courses, basic courses, supporting courses, and additional courses.